The effect of push-up and pull-up exercises on shooting performance of extracurricular handball players - Firmannudin, Firmannudin; Bhakti, Yopi Hutomo; Yulisatria, Guntur (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2025)
Handball is a sport that requires a combination of physical, technical, tactical and mental skills. One of the fundamental techniques that determines success in handball is shooting ability. This study aimed to analyse the effect of combining push-up and pull-up exercises on the shooting ability of extracurricular handball players. An experimental method with a pre-test–post-test control group design was employed. The participants consisted of 12 extracurricular handball players from SMA Negeri 3 Kotabumi, selected through purposive sampling and randomly assigned into two groups: an experimental group that received push-up and pull-up training and a control group that followed regular training. The intervention was conducted over six weeks with three training sessions per week. Shooting performance was evaluated using indicators of throwing distance and shooting accuracy. The results of paired sample t-tests indicated significant improvements in both throwing distance (t = 16.52) and shooting accuracy (t = 14.77) in the experimental group (p < 0.05), accompanied by large effect sizes (Cohen’s d > 0.80). Furthermore, independent sample t-tests revealed significant differences between the experimental and control groups (p < 0.05). These findings demonstrate that the combined push-up and pull-up training program is effective in enhancing shooting performance among extracurricular handball players.